2016
DOI: 10.4172/2161-038x.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia among Women of Reproductive Age, an Important Public Health Problem: Situation Analysis

Abstract: Background: Iron deficiency is a major cause of anemia and is more prevalent in developing countries, posing additional burden on health care systems, in the presence of scarcity of resources. The high-risk group consists of females and children but comparatively it is higher in females due to physiological reasons. Multiple factors can predict anemia, which in turn leads to various adverse outcomes. Objective: The purpose of this literature review was to review and synthesize the findings from literature abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 19 publications
5
66
0
Order By: Relevance
“…Evidence suggests that improved economic status is associated with appropriate nutrition conditions (27), lower infection morbidity (26), increased access to health services as well as other favourable living conditions (27,28), all of which in turn influence anemia. Malnourished women have greater risk of iron deficiency, the most common proximate cause of anemia (1) and malnutrition is often associated with poor socio-economic status (29). Interventions that aim to empower women economically should be considered in order to reduce anemia prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that improved economic status is associated with appropriate nutrition conditions (27), lower infection morbidity (26), increased access to health services as well as other favourable living conditions (27,28), all of which in turn influence anemia. Malnourished women have greater risk of iron deficiency, the most common proximate cause of anemia (1) and malnutrition is often associated with poor socio-economic status (29). Interventions that aim to empower women economically should be considered in order to reduce anemia prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is a multifaceted problem where nutrition and economic status work in synergy. Evidence suggested that improved economic status was associated with appropriate nutrition conditions (26), lower infection morbidity (25), increased access to health services as well as other favourable living conditions (26,27), all of which influence anemia. Malnourished women have greater risk of iron deficiency -the most common proximate cause of anemia (1) and they are mostly associated with poor socio-economic status (28).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetarian diets have become more common in developed countries where people are advised to eat more vegetables to reduce the incidence of non-communicable diseases including obesity (Turner-McGrievy, Mandes, & Crimarco, 2017), diabetes (Pawlak, 2017) and cardiovascular diseases (Keung & Owen, 2004) as well as environmental concerns associated with meat production. Although the beneficial effects of a vegetarian diet are well recognised, there is a risk of non-haem iron deficiency anaemia (Mawani, Ali, Bano, & Ali, 2016;Cairo, Silva, Bustani, & Marques, 2014). Iron deficiency leads to inflammation (Nunes & Tátá, 2017), impaired immune (Hassan et al, 2016) and endocrine (Maldonado-Araque et al, 2018) functions.…”
Section: Introductionmentioning
confidence: 99%